2014
DOI: 10.2106/jbjs.m.00105
|View full text |Cite
|
Sign up to set email alerts
|

Total Knee Arthroplasty After Previous Knee Surgery

Abstract: Background: With more than 650,000 knee arthroscopies and 175,000 anterior cruciate ligament reconstructions per-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(39 citation statements)
references
References 19 publications
1
37
1
Order By: Relevance
“…45 Furthermore, patients who have had previous knee surgery undergo total knee replacement at a substantially younger age than those without previous knee surgery. 46 unanswered questions and future research The common presumption that individuals with traumatic tears experience greater improvements in patient reported outcomes than those with degenerative tears after arthroscopic partial meniscectomy was not supported by our results. Given the lack of effect of arthroscopic partial meniscectomy compared with placebo surgery for degenerative meniscal tears, 43 and the positive effects of exercise for patients with degenerative meniscal tears 29 and anterior cruciate ligament injury, 28 the efficacy of arthroscopic partial meniscectomy for traumatic meniscal tears should be compared in controlled trials with placebo or non-operative treatment such as exercise.…”
Section: Meaning Of the Studycontrasting
confidence: 59%
“…45 Furthermore, patients who have had previous knee surgery undergo total knee replacement at a substantially younger age than those without previous knee surgery. 46 unanswered questions and future research The common presumption that individuals with traumatic tears experience greater improvements in patient reported outcomes than those with degenerative tears after arthroscopic partial meniscectomy was not supported by our results. Given the lack of effect of arthroscopic partial meniscectomy compared with placebo surgery for degenerative meniscal tears, 43 and the positive effects of exercise for patients with degenerative meniscal tears 29 and anterior cruciate ligament injury, 28 the efficacy of arthroscopic partial meniscectomy for traumatic meniscal tears should be compared in controlled trials with placebo or non-operative treatment such as exercise.…”
Section: Meaning Of the Studycontrasting
confidence: 59%
“…[5] It is increasingly recognized that the acute injury to the ACL signals the onset of a molecular stage of the disease process where an early therapeutic intervention could be useful,[6,7] particularly if the molecular processes that are elicited in the joint tissues at the time of injury are known. [8]…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, among ACL-injured patients undergoing ACL reconstruction, being younger and male had a protective effect on the risk of knee arthroplasty [43]. A recent study reported that patients with a history of ACL reconstruction underwent TKR at a younger age (average 50.2 years) than those who underwent other knee surgeries (average 59.9 years), including arthroscopy, meniscectomy, open reduction and internal fixation, chondroplasty, tibial tubercle transfer, and osteotomy [44]. Other studies have reported that patients with prior ACL reconstruction who underwent TKR were younger (average 58.1 years) than patients without ACL injury or prior knee surgery who underwent TKR (average 63.4 years), but this difference was not significant [45].…”
Section: Discussionmentioning
confidence: 99%